2018
DOI: 10.1016/j.idc.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Fever in the Returning Traveler

Abstract: Millions of children travel annually, whether they are refugees, international adoptees, visitors, or vacationers. Although most young travelers do well, many develop a febrile illness during or shortly after their trips. Approaching a fever in the returning traveler requires an appropriate index of suspicion to diagnose and treat in a timely manner. As many as 34% of patients with recent travel history are diagnosed with routine infections, but serious infections such as malaria, enteric fever, and dengue fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Diagnosis of febrile illnesses in travelers and people living in areas endemic for mosquito-borne diseases is a global challenge. There is a highly diverse group of etiological agents and diseases to consider, such as malaria, dengue, and enteric fevers [ 1 ]. Several of the mosquito-borne microbes are clinically important viruses, such as dengue (DENV), Zika (ZIKV), West Nile (WNV), and chikungunya viruses (CHIKV).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of febrile illnesses in travelers and people living in areas endemic for mosquito-borne diseases is a global challenge. There is a highly diverse group of etiological agents and diseases to consider, such as malaria, dengue, and enteric fevers [ 1 ]. Several of the mosquito-borne microbes are clinically important viruses, such as dengue (DENV), Zika (ZIKV), West Nile (WNV), and chikungunya viruses (CHIKV).…”
Section: Introductionmentioning
confidence: 99%
“…41 The majority of imported cases of malaria in the USA and European countries occur among immigrants and VFR travelers. 7 , 8 Children account for 11% to 23% of cases of imported malaria and the majority were associated with travel to Sub-Saharan Africa. 7 VFR children have 4 times higher risk of getting malaria than tourists.…”
Section: Major Tropical Causes Of Fevermentioning
confidence: 99%
“…It also should be considered in those who fail to improve with antibiotics for presumed bacterial pneumonia. 8 Children younger than 4 years of age are at risk of disseminated infection which may manifest as miliary tuberculosis or TB meningitis. Drug-resistant MTB is an increasing problem in different parts of the world.…”
Section: Major Tropical Causes Of Fevermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from other centres confirm that the most frequent diseases observed at arrival are dermatological conditions. Up to 70% of adoptees manifest at least one skin disease of which 57% are infectious .…”
mentioning
confidence: 99%